Transformation of Islamic Education in the Era of Artificial Intelligence: An Ethical Review of the Use of Technology in the Curriculum - Farhan, Muhammad; Ali, Mohamad; Hafidz, Hafidz (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This research aims to analyze how AI affects the Islamic education curriculum and identify the ethical challenges that arise in the process. The approach used is Systematic Literature Review (SLR) based on the PRISMA guidelines by searching literature through the Scopus database using a combination of keywords